Composition and Type of a Binder Effects on the Stainless Steel Foam Microstructure Prepared by Sponge Replication Method - Mat Noor, Fazimah; Abu Bakar, Muhamad Iqbar; Mohamad, Zaleha; Ismail, Al Emran; Ismon, Maznan; Ahmad, Sufizar; Abd Wahab, Hamani; Main, Nor Mazlana; Sanusi, Shahmir Hayyan (International Journal of Integrated Engineering, 2019)
Biomaterials with a porous structure are beneficial for a wide range of medical engineering applications such as filtration, bone replacement and implant development. Stainless Steel 316L (SS316L) foam has been fabricated by foam replication method at different SS316L powder composition which is 60 wt%, 65 wt%, and 70 wt%. The binders used were Polyethylene Glycol (PEG), Carboxymethyl Cellulose (CMC) and Polyvinyl Alcohol (PVA), while distilled water was used as a solvent. The effects of using different composition of SS36L powder, binders and sintering time to the SS316L foam properties was studied. The materials were mixed by using a mechanical stirrer at 250 rpm for 1 hour. Polyurethane foam (PU) which was used as a sacrificial template was dipped into the SS316L slurry until fully coated. The coated samples were then dried in a drying oven within 24 hours before being sintered in an argon gas environment at 1200Â°C. The samples were characterized to observe the microstructure of the SS316L foam produced. As expected, the viscosity of the SS316L slurry was increased as the SS316L composition increases. The viscosity of SS316L slurry prepared by using PVA as a binder is higher than the SS316L slurry prepared with CMC and PEG as binder. The SS316L foam produced consisted of a large volume of open and interconnected pores especially at higher SS316L composition.